Implementasi Strategi Transformasi Digital untuk Mengatasi Kesenjangan Distribusi Dokter Spesialis di Indonesia - Purwadhi Purwadhi; Yani Restiani Widjaja; Ratna Indriana Donggori; Raka Indrabrata Setiawan (Lembaga Pengembangan Kinerja Dosen, 2026)
The disparity in the distribution of specialist doctors in Indonesia is a structural challenge that creates disparities in access and quality of healthcare services between urban and rural/underdeveloped areas. The government addresses this issue through the Health System Transformation agenda, with the sixth pillar, Health Technology Transformation, as a key strategy. This study aims to analyze how the implementation of digital transformation strategies, specifically telemedicine supported by the SATUSEHAT ecosystem and Electronic Medical Records (RME), can be an effective solution to mitigate these challenges. Using systematic literature observation and SWOT analysis, this study examines Indonesia's digital ecosystem, compares it with best practices from Australia and Canada, and identifies critical success factors. The analysis shows that despite strong political commitment and an initial regulatory framework, implementation faces significant challenges related to digital infrastructure disruption, variability in healthcare human resource competencies, and data security issues. International case studies highlight the importance of a clear vision, stakeholder ownership, adaptable models, and operational efficiency. It concludes that digital transformation has significant potential to mitigate geographic challenges, but its success must rely on a holistic approach that integrates infrastructure strengthening, massive human resource capacity development, cybersecurity assurance, and the design of sustainable financing models. Strategic recommendations are formulated for macro-policy and managerial empowerment at the health facility level. Strengthening cross-sector collaboration, including public-private partnerships, is crucial for accelerating the adoption of digital technology in primary healthcare. Furthermore, adaptive monitoring and evaluation mechanisms are needed to ensure the transformation is aligned with the local context and population needs.